OBJECTIVE ELEMENTS OF THE LEGAL STRUCTURE OF AN ADMINISTRATIVE OFFENSE (MISDEMEANOR) FOR BULLYING IN UKRAINE - Приходько, Марина (SWorldJournal, 2021)
One of the socially negative phenomena in the educational environment is bullying. Reduction of its manifestations is possible, including due to a clear and practically applied rule of law. Therefore, the article considers the objective elements of the le